2019
DOI: 10.1016/j.jval.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Measuring Multiple Medication Adherence: A Systematic Review–Report of the ISPOR Medication Adherence and Persistence Special Interest Group

Abstract: these studies, 26 used proportion of days covered, 23 used medication possession ratio, and 72 used self-reported questionnaires (e.g., the Morisky Scale) to assess MMA. About 50% of the studies included more than one method for measuring MMA, and different variations of medication possession ratio and proportion of days covered were used for measuring MMA. Conclusions: There appears to be no standardized method to measure MMA. With an increasing prevalence of polypharmacy, more efforts should be directed towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 173 publications
5
92
0
Order By: Relevance
“…After applying the initial inclusion criteria for the systematic reviews, the full texts of 20 systematic reviews were obtained. Four were excluded after fulltext review, leaving 16 systematic reviews for data extraction (Vreeman et al, 2008;Elliott and Marriott, 2009;Vandenbroeck et al, 2011;AlGhurair et al, 2012;Paquin et al, 2013;Remor, 2013;Nguyen et al, 2014;Snyder et al, 2014;Akeroyd et al, 2015;Peŕez-Escamilla et al, 2015;Huang et al, 2016;Katusiime et al, 2016;Forbes et al, 2018;Pednekar et al, 2019;Pareja-Martinez et al, 2020;Plevinsky et al, 2020). From these 16 systematic reviews, 187 different adherence measures were extracted and coded.…”
Section: Resultsmentioning
confidence: 99%
“…After applying the initial inclusion criteria for the systematic reviews, the full texts of 20 systematic reviews were obtained. Four were excluded after fulltext review, leaving 16 systematic reviews for data extraction (Vreeman et al, 2008;Elliott and Marriott, 2009;Vandenbroeck et al, 2011;AlGhurair et al, 2012;Paquin et al, 2013;Remor, 2013;Nguyen et al, 2014;Snyder et al, 2014;Akeroyd et al, 2015;Peŕez-Escamilla et al, 2015;Huang et al, 2016;Katusiime et al, 2016;Forbes et al, 2018;Pednekar et al, 2019;Pareja-Martinez et al, 2020;Plevinsky et al, 2020). From these 16 systematic reviews, 187 different adherence measures were extracted and coded.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed adherence to ART using the pill count data, captured from patients’ re-fill chart and used for the purpose of clinical monitoring, together with clinicians’ report of skipped doses. Pill count is a valid method used to measure adherence to ART and has been used by several studies in resource limited settings [ 47 , 48 ]. Upon examination of the frequencies and distribution of our data, we found that the data were skewed towards high adherence.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for measuring adherence to treatment based on self-reported information may have certain limitations due to recall bias, social desirability and faults in self-observation [44]. However, the Morisky-Green test has been validated and has high specificity, a high positive predictive value and is easy to perform [27]; therefore, it is widely used.…”
Section: Limitationsmentioning
confidence: 99%